Faecal immunochemical test to triage patients with possible colorectal cancer symptoms: insights from the New Zealand FIT for symptomatic pilot - Saw, Kai Sheng; Ngatai, Lu-ana; Whiteside, Cathy; Parry, Susan; Bissett, Ian (Frontiers in Gastroenterology, 2025)
BackgroundThe New Zealand (NZ) FIT for Symptomatic Pilot (FSP) aimed to determine the feasibility of using faecal immunochemical test (FIT) as a triaging tool to assess patients presenting with symptoms suspicious for colorectal cancer (CRC).MethodsThis is a double-blinded diagnostic accuracy study conducted in two Health NZ Districts from July 2022 to January 2024. Consecutive adult patients referred with symptoms of suspected CRC, who were triaged for colonoscopy by endoscopists, were invited to perform a quantitative FIT. The diagnostic performance of FIT for CRC was assessed.ResultsValid FIT results were returned by 1,158 (82%) of 1,413 eligible patients; 1,043 were included in the diagnostic accuracy analysis. At low (“rule-out”) faecal haemoglobin (f-Hb) thresholds, the sensitivity and specificity for CRC were 93.8% (CI 79.2–99.2) and 75.9% (CI 73.1–78.5) for f-Hb ≥4 μg/g and 90.6% (CI 75.0–98.0) and 83.1% (CI 80.6–85.4) for f-Hb ≥10 μg/g. At a higher (“rule-in”) f-Hb threshold of ≥150 μg/g, the sensitivity and specificity for CRC were 78.1% (CI 60.0–90.7) and 95.9% (CI 94.4–97.0). The prevalence of CRC was 3.1%. At the lower limit of f-Hb detection, 73.7% of symptomatic patients had a negative FIT.ConclusionFSP demonstrated that FIT identified both a small group of symptomatic patients with a high risk of undiagnosed CRC for urgent investigation and the majority of symptomatic patients with a very low f-Hb who could avoid colonoscopy. Using FIT in this setting should protect patients from unnecessary colonoscopy, diagnose CRC earlier, and optimise colonoscopy utilisation.